Medical treatment of advanced malignant perivascular epithelioid cell tumors. Issue 4 (July 2020) - Fabbroni, Chiara; Sbaraglia, Marta; Sanfilippo, Roberta
Abstract : Purpose of review: Malignant PEComa are rare mesenchymal tumors characterized by genetic alterations actionable by target therapy. Indeed, they harbour loss of function of TSC1/TSC2, which lead to the activation of the mammalian target of rapamycin (mTOR) pathway, which is targetable therapeutically with mTOR inhibitors like sirolimus. A small subset of malignant PEComas instead harbor TFE3 gene fusions known to be mutually exclusive with TSC1/TSC2 loss-of-function mutations; therefore, leading to different therapeutic implication. Recent findings: mTOR inhibitors showed a response rate around 40% with a median PFS of 9 months both in retrospective case series than in phase 2 prospective clinical trials, therefore, representing the most active therapeutic drug. Up to now, the issue is the lack of further therapeutic lines in the advanced setting. Chemotherapy has a marginal role, while some responses were reported using Vascular endothelial growth factor-Tyrosine kynase inhibitors (VEGF-TKI) inhibitors. Summary: Malignant PEComas display some sensitivity to mTOR inhibitors. If progression thereto, no other drugs are available. Preclinical studies are ongoing to explore the potential combination of hormonal blockade in women and the potential use of PD1 checkpoint inhibitors.